Chemical Insights into Topical Agents in Intraocular Pressure Management: From Glaucoma Etiopathology to Therapeutic Approaches - Geewoo Nam Patton; Hyuck Jin Lee (MDPI AG, 2024)
Glaucoma encompasses a group of optic neuropathies characterized by complex and often elusive etiopathology, involvihttng neurodegeneration of the optic nerve in conjunction with abnormal intraocular pressure (IOP). Currently, there is no cure for glaucoma, and treatment strategies primarily aim to halt disease progression by managing IOP. This review delves into the etiopathology, diagnostic methods, and treatment approaches for glaucoma, with a special focus on IOP management. We discuss a range of active pharmaceutical ingredients used in glaucoma therapy, emphasizing their chemical structure, pharmacological action, therapeutic effectiveness, and safety/tolerability profiles. Notably, most of these therapeutic agents are administered as topical formulations, a critical aspect considering patient compliance and drug delivery efficiency. The classes of glaucoma therapeutics covered in this review include prostaglandin analogs, beta blockers, alpha agonists, carbonic anhydrase inhibitors, Rho kinase inhibitors, and miotic (cholinergic) agents. This comprehensive overview highlights the importance of topical administration in glaucoma treatment, offering insights into the current state and future directions of pharmacological management in glaucoma.